Microwave-power induced green synthesis of randomly oriented mesoporous anatase TiO2 nanoparticles for efficient dye sensitized solar cells. (1st May 2017) - Ullattil, Sanjay Gopal; Periyat, Pradeepan
Graphical abstract: Highlights: Microwave power induced green strategy for the synthesis of randomly arranged mesoporous anatase TiO2 nanoparticles. Efficient dye sensitized solar cells with 6.6% conversion efficiency under one Sun was obtained using above TiO2 nanoparticles. IPCE was increased from 50% to 55% under one Sun, when the microwave power irradiation changes from 300 to 600 W. Abstract: A facile and rapid synthesis of randomly distributed mesoporous anatase TiO2 nanoparticles for DSSC application using microwave method is reported here. Nanocrystalline anatase TiO2 is achieved by a sol microwave power strategy, where low microwave power intensity (300 and 600 W) for 5 min irradiation has been implemented. As synthesized anatase TiO2 nanoparticles have been characterized by a range of different techniques such as XRD, SEM, TEM and BET surface area analysis. These anatase TiO2 nanoparticles possessed high surface area up to 210 m 2 g −1 . Nanocrystalline nature and anatase phase purity were revealed from XRD. SEM studies have shown that the anatase TiO2 powder synthesized were appeared as spherical aggregates and the nano size of single particles (∼10 nm) were confirmed by TEM analysis. These anatase TiO2 nanoparticles were successfully employed as the working electrode for DSSC and a systematic investigation of the performance of DSSC constructed with standard N719 dye with conventional iodide/triiodide (I − /I3 − ) has demonstrated an efficiency of 6.6% under 100% sunlight with 55% of IPCE.